Heterogeneous microstructure of the bonding zone and its dependence on preheating in hybrid manufactured Ti-6Al-4V. Issue 10 (3rd October 2021) - Cui, Dingcong; Zhang, Yashan; He, Feng; Ma, Jiankai; Zhang, Kaiwei; Yang, Zhongsheng; Li, Junjie; Wang, Zhijun; Kai, Ji-jung; Wang, Jincheng; Jun, Feng
Abstract : Hybrid manufacturing (HM) Ti-6Al-4V components combining the advantages of forging and additive manufacturing were achieved. The bonding zone of the HMed component joins the substrate and the additive manufactured zone and its α′-α/α′/αm -α/β heterogeneous microstructure was attributed to the distinguishing cooling rate and pseudo-isothermal annealing temperature. The phase transformation mechanisms were clarified with a numerical simulation model for thermal analysis. Moreover, preheating manipulate the size, volume fraction and distribution of α′/αm /α phases to tailor the heterogeneous microstructure. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Preheating can serve as an effective way to tailor the heterogeneous microstructure in the bonding zone of HMed Ti-6Al-4V by affecting the cooling rate and pseudo-isothermal annealing temperature.